1998
DOI: 10.1080/136588198242003
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of local topographic variables derived from digital elevation models

Abstract: We study the accuracy of data on some local topographic attributes derived from digital elevation models (DEMs). First, we carry out a test for the precision of four methods for calculation of partial derivatives of elevations. We ® nd that the Evans method is the most precision algorithm of this kind. Second, we produce formulae for root mean square errors of four local topographic variables (gradient, aspect, horizontal and vertical landsurface curvatures), provided that these variables are evaluated with th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
142
0
5

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 256 publications
(151 citation statements)
references
References 18 publications
4
142
0
5
Order By: Relevance
“…provides the most precise estimate of topographic variables in the presence of elevation 880 errors (Florinsky 1998…”
Section: In Summary Although There Is a Clear Correlation Of The Difmentioning
confidence: 99%
See 2 more Smart Citations
“…provides the most precise estimate of topographic variables in the presence of elevation 880 errors (Florinsky 1998…”
Section: In Summary Although There Is a Clear Correlation Of The Difmentioning
confidence: 99%
“…This fitting provides an easy 872 calculation of the first and second derivate of the surface used to calculate the slope, theThe polynomial (Eq. A1) approximates the z coordinates of the 3×3 submatrix 875 rather than passing exactly through these values (Florinsky 1998). This leads to some 876 smoothing of the z function within the 3×3 submatrix, that is, a low-pass filtering that 877 can provide more correct calculation of derivative (Florinsky 1998).…”
Section: In Summary Although There Is a Clear Correlation Of The Difmentioning
confidence: 99%
See 1 more Smart Citation
“…SRTM or GLOBE DEMs, Jarvis et al, 2006;Hastings and Dunbar, 1998) to resolutions as low as 5, 10 or even 20km. The smoothing effect this resampling has on topography and consequently on any associated parameter has been widely noted and the subject of a number of experiments, ranging from calculation of derivatives (Florinsky, 1998;Zhang et al, 1999) to effects on spatial variability of parameters (Hu and Islam, 1997) and automatic analysis for environmental modelling (Albani et al, 2004). In hydrology, effects of scale and consequently methods to minimise these effects have been explored, for example by Armstrong and Martz (2003).…”
Section: Resolution Effects and Uncertaintymentioning
confidence: 99%
“…Gao (1997) studied the influence of spatial resolution at the micro-scale of three 1 km 2 areas representing a valley, a peak and a ridge; he reports that resolution has little influence on mean gradient, but affects significantly the standard deviation of slope, especially for a simple terrain. Florinsky (1998) mapped the root mean square errors (RMSE) of the local topographic variables slope, aspect, plan and profile curvatures, in order to analyse their accuracy. He concluded that high data errors on these variables are typical for flat areas.…”
Section: Previous Workmentioning
confidence: 99%